Simulating Molecular Interactions of Carbon Nanoparticles with a Double-Stranded DNA Fragment - Zhuang Wang; Hao Fang; Se Wang; Fan Zhang; Degao Wang (Journal of Chemistry)
Molecular interactions between carbon nanoparticles (CNPs) and a double-stranded deoxyribonucleic acid (dsDNA) fragment were investigated using molecular dynamics (MD) simulations. Six types of CNPs including fullerenes (C60 and C70), (8,0) single-walled carbon nanotube (SWNT), (8,0) double-walled carbon nanotube (DWNT), graphene quantum dot (GQD), and graphene oxide quantum dot (GOQD) were studied. Analysis of the best geometry indicates that the dsDNA fragment can bind to CNPs through pi-stacking and T-shape. Moreover, C60, DWNT, and GOQD bind to the dsDNA molecules at the minor groove of the nucleotide, and C70, SWNT, and GQD bind to the dsDNA molecules at the hydrophobic ends. Estimated interaction energy implies that van der Waals force may mainly contribute to the mechanisms for the dsDNA-C60, dsDNA-C70, and dsDNA-SWNT interactions and electrostatic force may contribute considerably to the dsDNA-DWNT, dsDNA-GQD, and dsDNA-GOQD interactions. On the basis of the results from large-scale MD simulations, it was found that the presence of the dsDNA enhances the dispersion of C60, C70, and SWNT in water and has a slight impact on DWNT, GQD, and GOQD.